B cell deficiency promotes the initiation and progression of lung cancer - Wu, Han; Chen, Chen; Gu, Lixing; Li, Jiapeng; Yue, Yunqiang; Lyu, Mengqing; Cui, Yeting; Zhang, Xiaoyu; Liu, Yu; Zhu, Haichuan; Liao, Xinghua; Zhang, Tongcun; et al. (Frontiers in Oncology, 2022)
Currently commercialized CAR-T cell therapies targeting CD19 and BCMA show great efficacy to cure B cell malignancies. However, intravenous infusion of these CAR-T cells severely destroys both transformed and normal B cells in most tissues and organs, in particular lung, leading to a critical question that what the impact of normal B cell depletion on pulmonary diseases and lung cancer is. Herein, we find that B cell frequency is remarkably reduced in both smoking carcinogen-treated lung tissues and lung tumors, which is associated with advanced cancer progression and worse patient survival. B cell depletion by anti-CD20 antibody significantly accelerates the initiation and progression of lung tumors, which is mediated by repressed tumor infiltration of T cells and macrophage elimination of tumor cells. These findings unveil the overall antitumor activity of B cells in lung cancer, providing novel insights into both mechanisms underlying lung cancer pathogenesis and clinical prevention post CAR-T cell therapy.